The effect of estrogen on craniofacial dimensions: a systematic review - Marjorie Ayumi Omori; Mirian Aiko Nakane Matsumoto; Raquel Assed Bezerra Segato; Léa Assed Bezerra da Silva; Paulo Nelson Filho; Erika Calvano Kuchler (University Library System, University of Pittsburgh, 2019)
Sex hormones have an effect on bone metabolism. However, it remains unclear how estrogen hormone affects mandible and maxilla growth and development. The aim of this study was to perform a systematic review to evaluate if estrogen is associated with developmental alterations in the maxilla/mandible phenotype. Material and methods: A computer search of the literature was performed using: Pubmed Medline (1966 - August 2018), Google Scholar and manual searching. A combination of the terms 'estrogens', 'mandible', 'dental arch', 'maxilla', 'craniofacial', 'growth' and 'development' was used. Studies that used animal models to evaluate the role of estrogen during growth and development on the dimensions of the maxilla and/or mandible were included. Results: 5 studies were selected to compose this systematic review. One study used zebrafish as a model. Two studies used female mice and 2 studies used female rats as a model. Two studies treated the animals with estrogen. Four studies demonstrated that estrogen has an effect on mandible dimension and 2 studies demonstrated that estrogen has an effect on maxilla. One study did find an association between estrogen deficiency and mandible/maxilla dimensions Conclusion: The current evidence suggested that both, increased and decreased levels of estrogen, have an effect on the maxilla and mandible dimensions.